Pendekatan Hermeneutika Dalam Penafsiran Al Qur’an: Makna Dan Sejarah Hermeneutika Untuk Penafsiran Al Qur’an - Ghozali (Yayasan Al-Afif, 2025)
Interpretation of the Qur'an is an intellectual and spiritual process that demands careful and contemporary methods. One approach that has developed in modern exegetical discourse is hermeneutics. This study aims to examine the meaning and historical development of hermeneutics and its relevance to Qur'anic interpretation. Hermeneutics, which initially developed in the Western tradition as a method for understanding classical texts and scriptures, is now being adopted by some Muslim thinkers to understand the Qur'an in its ever-changing social and cultural context. Using qualitative methods based on literature, this study explores the historical-philosophical significance of hermeneutics in contemporary Islamic studies. This study finds that the hermeneutic approach, when used carefully and proportionately, can open up a dialogue between the Qur'anic text and contemporary reality, without neglecting normative Islamic values. The results also highlight the differences in the approaches of these figures in combining traditional understanding and contextual approaches. Thus, the hermeneutic approach can be a methodological alternative in interpreting the Qur'an that is dynamic and contributes to the development of modern Islamic thought.